The Effect of Board Characteristics on Environmental, Social, and Governance Disclosure - Raika Dwi Rahayu; Raldyaz Prayogi (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to obtain empirical evidence on the influence of board gender diversity and independent commissioners on environmental, social, and governance disclosure with board size as a moderation variable. Design/methodology/approach – This study uses a type of quantitative research. The sample in this study is the infrastructure sector companies listed on the Indonesia Stock Exchange in 2022-2024 as many as 48 companies. The analysis technique used to test the hypothesis is multiple regression analysis using the Eviews 9 software. Findings – The results of this study found that board gender diversity had a positive and statistically significant effect on environmental, social, and governance disclosure, while independent commissioners had a positive and statistically insignificant effect on environmental, social, and governance disclosure, and board size had a positive and statistically significant effect on environmental, social, and governance disclosure. Research limitations/implications – This study is limited to the 2022-2024 observation period and uses only three independent variables, so it does not include other factors such as profitability and company size. The practical implication is that management needs to optimize the board structure and oversight functions to support sustainability strategies and long-term value creation. JEL : G34, M14, J16, Q56